THE INDONESIAN EFL STUDENTS’ ATTITUDES TOWARD THEIR L1-ACCENTED ENGLISH - Alimin Adi Waloyo; J Jarum (Erudio Journal of Educational Innovation, 2019)
In an international communication context, English becomes an International language , commonly known as English as an International Language (EIL). EIL sees various English accents equally because intelligibility, being able to deliver message clearly to listeners, is the main goal in a communication. Therefore, Indonesian EFL (English as a foreign language) students need to focus their English mastery on intelligibility over native-likeness accent when learning English. However, whether or not the students concentrate their English learning more on intelligibility is still unknown yet. To identify which aspects EFL students focus on, the research examined Indonesian EFL students’ attitudes toward their L1-accented English. The main aim is to enhance their awareness that intelligibility is the key component in an English communication. Also, English teachers hopefully discuss the intelligibility in their teaching. Thus, the targeted learning results, particularly related to speaking skills development, are more reachable so the students are more encouraged to develop their English. The study involved 46 students (14 males and 32 females) from University of Muhammadiyah Malang (UMM), East Java. The implemented instrument as a data collection is a questionnaire. The collected data were organized and then analyzed to find out EFL students’ attitudes perceiving their Indonesian-accented English. The researcher figured out that EFL students had less positive attitude towards their own English accent. That perception might be caused by their low linguistic awareness, excessive exposure to the Internet (YouTube, International news) made by native speakers of English. The result of data analysis will be elaborated to interweave the investigation outcomes with classroom context so the outcomes could be implemented in classroom instruction. Keywords: Accent, Intelligibility, EIL and attitude.